PENERAPAN BUKU CERITA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV DI SEKOLAH DASAR - Andi Zulfitriani; Rusdin Rusdin; Andi Nurfaizah; Rustam Rustam (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Reading comprehension is a fundamental skill for elementary school students in mastering various learning materials. However, the learning conditions in Grade IV at SDN Inpres 1 Lolu Palu indicate that students still experience difficulties in understanding the meaning of texts, identifying key information, and retelling the content in their own words. This situation prompted the use of picture storybooks as a learning medium that is more appropriate to students' learning characteristics. This study explores how picture storybooks are implemented during the learning process and describes the changes in students' reading comprehension skills following their use. The research employed a descriptive qualitative approach. Data were collected through classroom observations, interviews, documentation, and assessments of students' reading comprehension skills. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The learning process involved introducing the story, conducting picture walks, engaging students in active reading, facilitating discussions, and encouraging students to retell the story, all of which align with the principles of using picture storybooks in reading comprehension instruction. The implementation of these stages resulted in improvements in students' ability to comprehend texts, identify important information, answer comprehension questions, and retell stories using their own words. Therefore, picture storybooks can be considered an effective alternative instructional medium for enhancing reading comprehension learning in elementary schools. ABSTRAK Kemampuan memahami bacaan menjadi fondasi penting bagi siswa sekolah dasar dalam menguasai berbagai materi pembelajaran. Namun, kondisi pembelajaran di kelas IV SDN Inpres 1 Lolu Palu memperlihatkan bahwa peserta didik masih mengalami kesulitan dalam menangkap makna bacaan, mengidentifikasi informasi utama, serta menyampaikan kembali isi teks dengan bahasa mereka sendiri. Situasi tersebut mendorong pemanfaatan buku cerita bergambar sebagai media yang lebih sesuai dengan karakteristik belajar siswa. Kajian ini menelusuri bagaimana media tersebut diterapkan selama proses pembelajaran sekaligus menggambarkan perubahan kemampuan membaca pemahaman yang muncul setelah penggunaannya. Penelitian dilaksanakan dengan pendekatan kualitatif deskriptif. Informasi penelitian dihimpun melalui observasi, wawancara, dokumentasi, serta penilaian terhadap kemampuan membaca siswa, kemudian dianalisis menggunakan model Miles dan Huberman melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Proses pembelajaran berlangsung melalui pengenalan cerita, kegiatan picture walk, membaca secara aktif, diskusi, hingga menceritakan kembali isi cerita, yang seluruhnya sejalan dengan konsep penerapan buku cerita bergambar dalam pembelajaran membaca pemahaman. Penerapan tahapan tersebut menunjukkan adanya peningkatan kemampuan siswa dalam memahami isi bacaan, menemukan informasi penting, menjawab pertanyaan, dan mengungkapkan kembali isi cerita menggunakan bahasa sendiri. Dengan demikian, buku cerita bergambar layak dipertimbangkan sebagai media alternatif untuk memperkuat pembelajaran membaca pemahaman di sekolah dasar.